Underhand Passing Ability of Middle School Extracurricular Volleyball Students: Push Up and Pull Up Exercises - Akhir, Muh.; Suwardi, Suwardi; Hudain, Muh. Adnan; Fahrizal, Fahrizal; Kamaruddin, Ilham (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study aims to determine how push-up and pull-up exercises affect the underhand passing ability in volleyball games among middle school students participating in extracurricular activities, as well as to identify the differences in effectiveness between these two types of exercises. The study used an experimental method with a pre-experimental pretest-posttest design. The research sample comprised 18 volleyball extracurricular participants from Public Middle School 3 Mare, divided into two training groups. The instrument used was the Brumbach Forearm Pass Wall-Volley Test. The training program lasted for four meetings per week. The data analysis was conducted using the Shapiro-Wilk normality test, a homogeneity test, and a paired sample t-test with a significance level of 5%, all performed with SPSS 22.0. The results showed a significant increase in underhand passing ability in both training groups (p = 0.000). The pull-up group experienced an increase in average score from 13.89 to 20.33 (an increase of 6.44 points), while the push-up category experienced an increase from 13.89 to 19.78 (an increase of 5.89 points). Comparative analysis indicated that pull-up training had a greater effect on improving underarm passing ability than push-up training. Both pull-up and push-up training were effective in improving the underarm passing ability of extracurricular students participating in volleyball games at middle school. However, pull-up training showed higher effectiveness because it involved muscle activation that was more relevant to underarm passing techniques and had a more specific movement pattern similarity to underarm passing skills in volleyball games.